Using Video and Multimodal Classroom Interaction Analysis to Investigate How Information, Misinformation, and Disinformation Influence Pedagogy - Riordan, John-Paul; Revell, Lynn; Bowie, Bob; Thomas, Caroline; Woolley, Mary; Hulbert, Sabina (Video journal of education and pedagogy, 2023)
Abstract Misinformation is accidentally wrong and disinformation is deliberately incorrect (i.e., deception). This article uses the Pedagogy Analysis Framework (paf) to investigate how information, misinformation, and disinformation influence classroom pedagogy. 95 people participated (i.e., one lesson with 7-year-olds, another with 10-year-olds, and three with a class of 13-year-olds). The authors used four video-based methods (lesson video analysis, teacher verbal protocols, pupil group verbal protocols, and teacher interviews). 35 hours of video data (recorded 2013-2020) were analysed using Grounded Theory Methods by the researchers, the class teachers, and groups of pupils (three girls and three boys). The methodology was Straussian Grounded Theory. The authors present how often participants used information, misinformation, and disinformation. They illustrate how the paf helps understand and explain information, misinformation, and disinformation in the classroom by analysing video data transcripts. In addition, the authors discuss participant perceptions of the status of information; overlapping information, misinformation, and disinformation; and information communication difficulties.